Pengaruh Kemampuan, Motivasi Belajar, dan Lingkungan Sekolah terhadap Prestasi Belajar Siswa SMPN Banjarmasin - Zaid Abdurrakhman, M.; Kadir, Abd.; Jayen, Fredy (Universitas Hang Tuah, 2021)
This study aims to analyze the effect of ability, learning motivation and school environment on student achievement at SMPN 17 Banjarmasin. The research method used is analytic survey. The type of research is explanatory research. The sample was 75 students. Data collection techniques used questionnaires, documentation, interviews and observations. Validity and reliability tests were carried out on the research instrument. Data were analyzed by multiple linear regression analysis. The results showed that the ability of teachers, students' learning motivation and the school environment partially and simultaneously had a significant effect on student achievement at SMPN 17 Banjarmasin. The contribution of the independent variable's influence on the ability of teachers, students' learning motivation and the school environment on learning achievement is 64.50%. Of the three independent variables, the school environment has a dominant influence on student achievement.